The Executive Regulations of The Income Tax Law = اللائحة التنفيذية لقانون الضريبة على الدخل - Egypt (2025)
Ministerial Decree No, 991 of the year 2005; Issuing the executive regulations of the income tax law promulgated by law No. 91 of the year 2005........... Book 1: General Provisions.......... Book 2: Income Tax On Natural Persons. Part-1: Part 2: Scope of tax enforceability and its rate. Salaries and the like........ Part-3: Commercial and industrial activity....... Page 1 3 7 7 9 18 Chapter 1: Taxable revenues.............. Chapter 2: Determination of the revenues included in the taxable 19 HS 18 base.. Chapter 3: Exemptions.. Part 4: Free profession revenues. Chapter 1: Determination of the revenues included in the taxable Chapter Real estate wealth revenues................... Part-5: 2: Exemption from the tax. Chapter 1: Taxable revenues.......... Chapter 2: Determination of the revenues included Book 3: Tax on juridical persons' profits: Part-1. Scope of tax enforceability....... Part-2: Determination of the taxable income..... Book-4: The tax withheld at source....... 25 27 all 27 in the taxable 29 31 31 34 41 Book-5: Deduction, collection, and advance payments for account de to of the tax.............. Part - 1: Commercial and industrial activity Chapter 1: Deduction...... Chapter 2: Advance payments......... Free professions-collection for account of the tax Part-2, Part 3: General provisions...m Book-6: Taxpayers' and others' obligations........ Part-1: Notification and bookkeeping..................…...….……..…...…...…... Part 2: Tax returns.... Part-3: Tax assessment. Part 4: Examination and investigation. 46 50 50 59 61